Evaluation of a suitable thin layer model for drying of pumpkin under forced air convection - Iroemeha, Onwude Daniel; Hashim, Norhashila; Janius, Rimfiel; Mat Nawi, Nazmi; Abdan, Khalina (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
The thin layer drying kinetics of pumpkin slices (Cucurbita moschata) were experimentally investigated in a convective hot air dryer. In order to select the appropriate model for predicting the drying kinetics of pumpkin (Cucurbita moschata), twelve thin layer semi theoretical, theoretical and empirical models, widely used in describing the drying behaviour of agricultural products were fitted to the experimental data. The Page and Two term exponential models showed the best fit under certain drying conditions. The Hii et al. (2009) model, which was adopted from a combination of the Page and Two term models was compared to the other 11 selected thin layer models based on the coefficient of determination (R2) and sum of squares error (SSE). Comparison was made between the experimental and model predicted moisture ratio by non-linear regression analysis. Furthermore, the effect of drying temperature and slice thickness on the best model constants was evaluated. Consequently, the Hii et al. (2009) model showed an excellent fit with the experimental data (R2 > 0.99 and SSE < 0.012) for the drying temperatures of 50, 60, 70 and 80 °C and at different sample thicknesses of 3 mm, 5 mm and 7 mm respectively. Thus, the Hii et al. (2009) model can adequately predict the drying kinetics of pumpkin.